OBTAINING CARBON ADSORBENTS BASED ON SECONDARY RAW MATERIALS AND STUDYING THEIR PHYSICAL AND CHEMICAL PROPERTIES (Scientific journal of the Fergana State University, 2024)
The article considers the production of carbon adsorbents based on secondary raw materials and their physicochemical properties. Special attention is paid to the study of natural coals, binder additives, synthetic reagents and industrialwaste that can be used in the production of carbon adsorbents. Further improvement of methods and technologies for theproduction of carbon adsorbents based on carbon-containing raw materials is one of the urgent tasks today. For this purpose, itis of particular importance to obtain carbon adsorbents from local secondary raw materials, including used car tires andmelamine paper waste. General information about raw materials is provided. According to the change in the pyrolysistemperature of the obtained carbon adsorbents, the mass loss was 60-65%, and the productivity of coal adsorbents was 35-40%. The moisture content of adsorbents is 3-5%, and the ash content is 7-12%. It is of practical importance that the formationof coal adsorbents is productive, and the amount of moisture and ash meets the requirements for carbon adsorbents. Based onthe study of colloidal-chemical and adsorption properties of the obtained carbon adsorbents and determination of structuralsorption parameters based on them, it is possible to recommend their use in various fields of the chemical industry